Accessing indenoazulenes via a gold-catalysed cyclisation of cycloheptatrienyl-substituted 1,5-diynes: very important publication - Mackenroth, Alexandra; Ahrens, Alexander; Wunsch, Jonas; Berger, Raphael; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2024)
Herein we report that cycloheptatrienyl-substituted 1,5-diynes with aromatic backbones undergo a gold-catalysed 5-endo-dig cyclisation to give 11H-indeno-[2,1-a]azulenes at room temperature. This methodology complements the established range of aromatic structures obtained from gold-catalysed conversions of differently substituted 1,5-diynes accessed via highly reactive cationic intermediates. We have demonstrated the scope of the reaction and have assessed the possibility of further functionalisation of the indenoazulene scaffold. Additionally, we have studied the optical and electrochemical properties as well as the frontier molecular orbitals of this structural motif by both spectroscopic and theoretical means.